Pengaruh Citra Merek dan Persepsi Kualitas terhadap Keputusan Pembelian Suzuki Satria F150 di Kabupaten Karawang - Faisal Cahya Pramudiya; Ajat Sudrajat (Universitas Proklamasi 45, 2021)
The automotive industry is a company engaged in the production of land transportation equipment, including motorcycles. The rapid development of the automotive industry is in line with the human need to move more dynamically. This study aims to determine the role of brand image and product quality perceptions on purchasing decisions for Suzuki Satria F150 motorcycle products in the Karawang Regency. This research is quantitative research that uses a preliminary study and a questionnaire as a data collection instrument. This study uses the formula of unknown populations to determine the number of samples. The sample used in this research is 96 respondents. The primary data that has been collected is processed using SPSS version 25. The results of this study found that brand image and product quality perceptions had a significant effect on purchasing decisions for Suzuki Satria F150 motorcycle products in Karawang Regency.